An Initial Approach to the Presence of Pharmaceuticals in Wastewater from Hospitals in Colombia and Their Environmental Risk (2022)
ABSTRACT: Hospital wastewater (HWW) from three different cities in Colombia was characterized. Wastewater quality indicators and 38 relevant pharmaceuticals were examined. The HWW had pH from 6.82 to 8.06, chemical oxygen demand was between 235.5 and 1203 mg L−1, and conductivity ranged from 276.5 to 717.5 μS cm−1. Additionally, most of the target pharmaceuticals (20 of 38) had 100% occurrence frequency in the samples due to their high and continuous consumption in the hospitals. Indeed, acetaminophen, diclofenac, azithromycin, ciprofloxacin, sulfamethoxazole, losartan, metoprolol, and omeprazole were present in all samples at concentrations from one up to some hundreds of μg L−1. Once pharmaceuticals are discharged into local sewage systems or rivers, because of the high dilution of HWW, the individual environmental hazards are low (i.e., risk quotients, RQ < 0.1 were determined). The action of conventional treatments on HWW also decreased the individual environmental risks of pharmaceuticals (RQ values < 0.1). However, the mixture of pharmaceuticals in the HWW had potential environmental risks (as RQ > 0.1 were found), remarking the need for efficient processes to eliminate pharmaceuticals from HWW. This work provides an initial view on the characterization of diverse Colombian HWW, which could be useful for the understanding of the current situation of pollution by pharmaceuticals in Latin America.